Proteomic Analysis of Endothelial Cells Exposed to Ultrasmall Nanoparticles Reveals Disruption in Paracellular and Transcellular Transport. Issue 5 (25th February 2019) - Kuruvilla, Jacob; Bayat, Narges; Cristobal, Susana
Abstract: The large interactive surfaces of nanoparticles (NPs) increase the opportunities to develop NPs for vascular targeting. Proteomic analysis of endothelial cells exposed to NPs reveals the cellular response and turns the focus into the impairment of the endothelial permeability. Here, quantitative proteomics and transcriptome sequencing are combined to evaluate the effects of exposure to sub‐lethal concentrations of TiO2 ‐USNPs and TiO2 ‐NPs on human dermal microvascular endothelial cells. Endothelial cells react to preserve the semi‐permeable properties that are essential for vascular tissue fluid homeostasis, vascular development, and angiogenesis. The main impact of the exposure was alteration of functional complexes involved in cell adhesion, vesicular transport, and cytoskeletal structure. Those are the core cellular structures that are linked to the permeability and the integrity of the endothelial tissue. Moreover, the extracellular proteins uptake along wih the NPs into the endothelial cells escape the lysosomal degradation pathway. These findings improve the understanding of the interaction of NPs with endothelial cell. The effects of the studied NPs modulating cell–cell adhesion and vesicular transport can help to evaluate the distribution of NPs via intravenous administration.